Does Age Younger Than 65 Affect Clinical Outcomes in Medicare Patients Undergoing Lumbar Fusion?. Issue 9 (23rd November 2022) - Karamian, Brian A.; Toci, Gregory R.; Lambrechts, Mark J.; Canseco, Jose A.; Basques, Bryce; Tran, Khoa; Alfonsi, Samuel; Rihn, Jeffery; Kurd, Mark F.; Woods, Barrett I.; Hilibrand, Alan S.; Kepler, Christopher K.; et al.
Abstract : Study Design: This was a retrospective cohort study. Objective: To determine if age (younger than 65) and Medicare status affect patient outcomes following lumbar fusion. Summary of Background Data: Medicare is a common spine surgery insurance provider, but most qualifying patients are older than age 65. There is a paucity of literature investigating clinical outcomes for Medicare patients under the age of 65. Materials and Methods: Patients 40 years and older who underwent lumbar fusion surgery between 2014 and 2019 were queried from electronic medical records. Patients with >2 levels fused, >3 levels decompressed, incomplete patient-reported outcome measures (PROMs), revision procedures, and tumor/infection diagnosis were excluded. Patients were placed into 4 groups based on Medicare status and age: no Medicare under 65 years (NM<65), no Medicare 65 years or older (NM≥65), yes Medicare under 65 (YM<65), and yes Medicare 65 years or older (YM≥65). T tests and χ 2 tests analyzed univariate comparisons depending on continuous or categorical type. Multivariate regression for ∆PROMs controlled for confounders. Alpha was set at 0.05. Results: Of the 1097 patients, 567 were NM<65 (51.7%), 133 were NM≥65 (12.1%), 42 were YM<65 (3.8%), and 355 were YM≥65 (32.4%). The YM<65 group had significantly worse preoperative Visual Analog Scale back ( P =0.01) and preoperative and postoperative Oswestry Disability Index (ODI), Short-Form 12 Mental Component Score (MCS-12), and Physical Component Score (PCS-12). However, on regression analysis, there were no significant differences in ∆PROMs for YM <65 compared with YM≥65, and NM<65. NM<65 (compared with YM<65) was an independent predictor of decreased improvement in ∆ODI following surgery (β=12.61, P =0.007); however, overall the ODI was still lower in the NM<65 compared with the YM<65. Conclusion: Medicare patients younger than 65 years undergoing lumbar fusion had significantly worse preoperative and postoperative PROMs. The perioperative improvement in outcomes was similar between groups with the exception of ∆ODI, which demonstrated greater improvement in Medicare patients younger than 65 compared with non-Medicare patients younger than 65. Level of evidence: Level III (treatment).